Powder cores and electronic components

By using epoxy resin with multiple mesogenic frames as adhesives, the problem of adhesion defects of powder cores during the temperature mold forming process is solved, and high strength, relative magnetic permeability and thermal stability are achieved, and powder cores suitable for high-frequency and high-temperature environments are suitable.

JP7670551B2Active Publication Date: 2025-04-30TDK CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021097228
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-10
Publication Date
2025-04-30
Estimated Expiration
2041-06-10

AI Technical Summary

Technical Problem

The existing powder cores are prone to adhesion defects during the forming process of the temperature mold, resulting in forming defects, and it is difficult to achieve high relative permeability, high strength and high thermal stability in the forming of the temperature mold.

Method used

Epoxy resin with at least two mesogenic frames is used as the adhesive, by adjusting the number and structure of the mesogenic frames, adhesion defects are avoided, and the strength, relative magnetic permeability and thermal stability of the powder core are improved.

Benefits of technology

It effectively avoids adhesion defects during the forming process of temperature molds, improves the strength, relative magnetic permeability and thermal stability of the powder core, making it suitable for high-frequency and high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670551000008
    Figure 0007670551000008
  • Figure 0007670551000009
    Figure 0007670551000009
  • Figure 0007670551000001
    Figure 0007670551000001
Patent Text Reader

Abstract

To provide a dust core having excellent specific permeability, strength, and heat resistance and an electronic component using the same.SOLUTION: A dust core 110 has a binder 2 including epoxy resin and magnetic particles 4 dispersed in the binder. The epoxy resin in the dust core 110 has at least two mesogenic skeletons between two epoxy bonds close to each other along a molecular chain.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder magnetic core and an electronic component including the powder magnetic core. [Background technology]

[0002] Known magnetic cores for magnetic electronic components such as inductors and reactors include powder magnetic cores as shown in Patent Document 1. These powder magnetic cores can be manufactured, for example, by kneading magnetic particles together with a binder and compression molding the mixture.

[0003] The binder melts and flows during the molding process and fills in between the magnetic particles, thereby bonding the magnetic particles together and providing electrical insulation. Therefore, the binder properties affect the density, strength, relative permeability, and other properties of the powder core, making it one of the important design factors for the powder core.

[0004] Representative binders used in dust cores include, for example, silicone resins, epoxy resins, phenolic resins, polyamide resins, polyimide resins, polysilazane resins, polyester resins, polycarbonate resins, water glass, and low-melting glass. Among these binders, epoxy resins have the advantages of excellent adhesive strength, electrical insulation, dimensional stability, and solvent resistance, being curable at low temperatures of 200° C. or less, and being readily available industrially at low cost, and are therefore widely and commonly used. In particular, Patent Document 1 discloses that dust cores with high relative magnetic permeability, high strength, and high thermal conductivity can be obtained by using an epoxy resin having a specific mesogen skeleton.

[0005] However, when conventional epoxy resins are used, molding defects such as the molded body sticking to the mold may occur depending on the molding conditions. In particular, when warm molding is performed to further improve the magnetic core density, the above-mentioned sticking defects are likely to occur. Therefore, there is a demand for the development of technology that can be used for warm molding and can more effectively achieve high relative magnetic permeability, high strength, and high heat resistance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-12671 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a powder magnetic core having excellent relative permeability, strength, and heat resistance, and an electronic component using the powder magnetic core. [Means for solving the problem]

[0008] In order to achieve the above object, a powder magnetic core according to the present invention comprises: A binder including an epoxy resin and magnetic particles dispersed in the binder, The epoxy resin has at least two mesogenic skeletons between two adjacent epoxy bonds along the molecular chain.

[0009] As a result of intensive research, the present inventors have found that the number of mesogen skeletons in an epoxy resin affects adhesion defects during warm molding. Specifically, according to experiments by the present inventors, when an epoxy resin having no mesogen skeleton or an epoxy resin having only one mesogen skeleton between epoxy bonds is used, the molded body is likely to stick to the mold during warm molding, and molding defects are likely to occur. For this reason, with these conventional epoxy resins, it was necessary to use a lubricant that could lead to a decrease in strength, or to manufacture the product by cold molding instead of warm molding. On the other hand, when an epoxy resin having at least two or more mesogen skeletons between epoxy bonds is used, adhesion defects during warm molding can be prevented. As a result, the dust core according to the present invention exhibits higher strength, relative permeability, and heat resistance than when a conventional epoxy resin is used.

[0010] Preferably, the magnetic particles are metal magnetic particles, and the content of the binder relative to 100 parts by mass of the metal magnetic particles is 1.0 part by mass or more and 4.0 parts by mass or less.

[0011] Preferably, the mesogenic skeleton has a structure represented by the following formula (I). [ka] In formula (I), Y is selected from -H, an alkyl group (an aliphatic hydrocarbon having 4 or less carbon atoms), an acetyl group, and a halogen, and all Y in the mesogenic skeleton may be the same or different. * indicates a bonding site with an adjacent atom.

[0012] The powder magnetic core of the present invention can be applied to various electronic components such as inductors, reactors, transformers, non-contact power supply coils, and magnetic shielding components, and is particularly preferably used as a magnetic core for inductors.

[0013] In an inductor having a powder magnetic core of the present invention, The volume resistance after storage at 175°C for 100 hours is R A The volume resistance before storage is R B Then, preferably, R A / R B >0.001. In the inductor of the present invention, an epoxy resin having two or more mesogen skeletons between epoxy bonds is contained in the powder magnetic core, thereby achieving the above-mentioned R A / R B As a result, the inductor of the present invention can reduce energy loss and favorably realize a smaller inductor size and a larger current capacity. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an inductor element according to one embodiment of the present invention. [Diagram 2]FIG. 2 is an enlarged cross-sectional view of a portion of the powder magnetic core shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.

[0016] As shown in FIG. 1, an inductor element 100 according to one embodiment of the present invention has a powder magnetic core 110 and a coil 120 embedded inside the powder magnetic core 110.

[0017] The shape of the powder core 110 is not particularly limited, and can be, for example, a cylindrical shape, an elliptical cylindrical shape, a rectangular cylindrical shape, or the like. As shown in Fig. 2, the powder core 110 contains a binder 2 as a binding material and magnetic particles 4 dispersed in the binder 2, and may also contain non-magnetic inorganic particles. That is, the powder core 110 is formed into a predetermined shape by binding a plurality of magnetic particles 4 via the binder 2. The binder 2 and the magnetic particles 4 constituting the powder core 110 will be described in detail below.

[0018] The binder 2 is mainly composed of cured epoxy resin and phenol resin, and may contain trace amounts of other organic components. Here, the "trace amount of organic components" refers to components resulting from lubricants, curing accelerators, flexibilizers, plasticizers, dispersants, colorants, anti-settling agents, etc., and may be contained in an amount of about 1.0 part by mass or less per 100 parts by mass of the epoxy resin, which is the main component of the binder 2.

[0019] In this embodiment, the epoxy resin of the binder 2 has a specific molecular structure. Specifically, the epoxy resin of the binder 2 has a plurality of mesogen skeletons between two epoxy bonds that are adjacent to each other along the molecular chain.

[0020] Here, the term "epoxy bond" in this embodiment means a molecular arrangement formed by ring-opening of an epoxy group present in a prepolymer by a polymerization reaction (curing reaction). Also, the term "mesogenic skeleton" is a general term for an atomic group that includes a polycyclic aromatic hydrocarbon or two or more aromatic rings and has rigidity and orientation.

[0021] More specifically, the mesogenic skeleton preferably has a partial structure represented by the following formula (J). [ka] In the above formula (J), X is a single bond or at least one linking group selected from the following group (A): [ka] In the above formula (J), Y is selected from -H (hydrogen), an alkyl group (an aliphatic hydrocarbon having 4 or less carbon atoms), an acetyl group, and a halogen, and all Y in the mesogenic skeleton may be the same or different. Furthermore, * in formula (J) represents a bonding site with an adjacent atom.

[0022] In particular, in this embodiment, it is more preferable that the mesogenic skeleton is a partial structure represented by the following formula (I). [ka] Y and * in the above formula (I) are the same as those in formula (J). That is, in the mesogenic skeleton shown in formula (I), X in formula (J) is a single bond, and the number of Y's on which functional groups (side chains such as alkyl groups, acetyl groups, and halogens) can be arranged is more limited than in formula (J).

[0023] The mesogen skeleton as described above is considered to act to increase the lubrication between the magnetic particles 4 during the molding process and to efficiently promote the rearrangement of the magnetic particles 4. In addition, stacking (molecular overlap) is likely to form between the mesogen skeletons after curing, and this stacking is considered to contribute to improving the mechanical strength of the binder 2 and the powder core 110. Furthermore, the mesogen skeleton is considered to act to reduce the thermal resistance between the magnetic particles 4. Therefore, by forming the powder core 110 from an epoxy resin containing a mesogen skeleton, improvements in density, strength, relative permeability, thermal conductivity, and the like can be expected. Note that in the above, "rearrangement of the magnetic particles 4" means that the particles move due to pressure and approach a close-packed state.

[0024] In the epoxy resin of the binder 2 in this embodiment, at least two (preferably 10 or less, more preferably 3 or less) mesogenic skeletons as described above are present between two epoxy bonds adjacent to each other along the molecular chain. The upper limit of the number of mesogenic skeletons present between the epoxy bonds is not particularly limited, and may be, for example, 100 or less. The multiple mesogenic skeletons present between adjacent epoxy bonds may be different from each other, or may all have the same structure. In addition, the multiple mesogenic skeletons between the two adjacent epoxy bonds may be connected continuously by a single bond, or may be connected via a single or multiple linking groups.

[0025] Here, the "two epoxy bonds adjacent to each other" will be explained in more detail. The molecular structure having multiple mesogen skeletons as described above can be realized, for example, by curing an epoxy resin having a prepolymer as shown in the following formula (K). [ka] In the prepolymer shown in formula (K), E1 and E2 located at the ends are both epoxy groups. Additionally, M1 and M3 in formula (K) are mesogenic skeletons. When an epoxy resin containing the prepolymer of formula (K) is cured, the epoxy groups of E1 and E2 open and a polymer chain is formed. In this case, the space between the open E1 and E2 corresponds to "two epoxy bonds that are close to each other along the molecular chain," and "one (M1) + n (M3)" mesogenic skeletons exist between these epoxy bonds.

[0026] If only a single mesogen skeleton is present between two adjacent epoxy bonds, molding defects such as the molded body sticking to the die during warm molding are likely to occur. On the other hand, as described above, if multiple mesogen skeletons are present between adjacent epoxy bonds, sticking defects can be suppressed, and the powder core 110 can be manufactured not only by cold molding but also by warm molding. In other words, the powder core 110 of this embodiment contains an epoxy resin having two or more mesogen skeletons between the epoxy bonds, and thus has higher strength, relative permeability, and heat resistance than an epoxy resin having only a single mesogen skeleton.

[0027] The number of mesogenic skeletons present between epoxy bonds can be identified by analyzing the molecular structure of the binder 2. For example, the molecular structure of the binder 2 can be analyzed by appropriately combining nuclear magnetic resonance spectroscopy (NMR), Fourier transform infrared spectroscopy (FT-IR), gas chromatography mass spectrometry (GC / MS), liquid chromatography mass spectrometry (LC / MS), etc. A measurement sample can be prepared by collecting the binder 2 from the powder core 110 shown in FIG. 1.

[0028] In this embodiment, the magnetic particles 4 may be oxide magnetic particles such as soft ferrite, but are preferably soft magnetic metal magnetic particles. Examples of soft magnetic metal magnetic particles include pure iron, Fe-Si alloys (iron-silicon), Fe-Al alloys (iron-aluminum), Permalloy alloys (Fe-Ni), Sendust alloys (Fe-Si-Al), Fe-Si-Cr alloys (iron-silicon-chromium), Fe-Si-Al-Ni alloys, Fe-Ni-Si-Co alloys, Fe-based amorphous alloys, and Fe-based nanocrystalline alloys.

[0029] It is preferable to form an insulating coating on the surface of the soft magnetic metal magnetic particles as described above. Examples of the insulating coating include a coating (oxide film) formed by oxidation of the particle surface layer, a phosphate coating, a silicate coating, a glass coating, an inorganic coating containing BN, SiO2, MgO, Al2O3, etc., or an organic coating. These insulating coatings can be formed by surface treatments such as heat treatment, phosphate treatment, mechanical alloying treatment, silane coupling treatment, and hydrothermal synthesis. By forming an insulating coating on the soft magnetic metal magnetic particles, the high-frequency loss of the dust core 110 can be suppressed.

[0030] The average particle size (D50) of the magnetic particles 4 is not particularly limited and can be, for example, 50 μm or less, and is preferably within the range of 20 μm to 40 μm. The average particle size of the magnetic particles 4 may be measured by performing image analysis on a cross section of the powder core 110 as shown in FIG. 2. Specifically, the area of ​​each particle included in the cross section as shown in FIG. 2 is measured, and the equivalent circle diameter of each particle is calculated from the area value, thereby obtaining the particle size distribution of the magnetic particles 4. In this measurement, the dimensions of the measurement field may be appropriately adjusted according to the particle size of the magnetic particles 4 to be observed, and it is preferable to perform analysis in at least five fields of view to obtain the particle size distribution.

[0031] The magnetic particles 4 contained in the powder magnetic core 110 may all be made of the same material, or may be made up of a plurality of particle groups made of different materials. Also, as shown in Fig. 2, the magnetic particles 4 may be made up of a plurality of particle groups with different particle sizes. For example, the magnetic particles 4 can be made up of a mixture of large particles 4a made of an Fe-Si alloy and small particles 4b made of pure iron and having an average particle size smaller than that of the large particles 4a.

[0032] Furthermore, the average circularity of the magnetic particles 4 in the cross section of the powder core 110 is not particularly limited, but in consideration of the DC superposition characteristics, the average circularity of the magnetic particles 4 is preferably high, at 0.9 or more, and more preferably 0.95 or more. The average circularity of the magnetic particles 4 can be measured by performing image analysis on the cross section of the powder core 110 as shown in FIG. 2. Specifically, the area S and the length L of the contour line of each magnetic particle 4 included in the cross section image are measured, and the circularity is calculated based on the following formula. This measurement is performed on at least 50 magnetic particles 4 to obtain a circularity distribution, and the circularity at a cumulative frequency of 50% is calculated as the average circularity. Circularity = 4πS / L 2

[0033] Here, we will provide additional information on the relationship between the average circularity of the magnetic particles 4 and the strength of the powder core 110. In the case of spherical magnetic particles with a high average circularity as described above, entanglement between adjacent particles, known as the anchor effect, is less likely to occur, and the strength of the powder core generally decreases. In the powder core 110 of this embodiment, even when magnetic particles 4 with a high circularity are used, it is possible to obtain high strength by including an epoxy resin having multiple mesogen skeletons between the epoxy bonds.

[0034] Furthermore, when the magnetic particles 4 are metal magnetic particles, the content of the binder 2 in the powder core 110 is preferably 4.0 parts by mass or less, and more preferably 1.0 to 4.0 parts by mass, relative to 100 parts by mass of the magnetic particles. In the powder core 110 of this embodiment, by using an epoxy resin having multiple mesogen skeletons between epoxy bonds, shape retention can be ensured and high strength can be obtained even if the ratio of the binder 2 to the magnetic particles 4 is reduced. Furthermore, by setting the content of the binder 2 within the above range, it is possible to achieve and improve both high strength and high magnetic properties.

[0035] The binder content can be roughly estimated by analyzing the powder core with an inductively coupled plasma atomic emission spectroscopy (ICP-AES). In this case, the powder core is dissolved in, for example, hydrochloric acid to prepare an analytical sample, and the binder content is calculated by roughly estimating the intensity of the elements detected by ICP-AES.

[0036] The inductor element 100 having the powder magnetic core 110 containing the binder 2 and the magnetic particles 4 described above has excellent heat resistance. Specifically, the volume resistance of the inductor element 100 after storing it at 175° C. for 100 hours is R A The volume resistance before storage is R B Then, R A / R B It is preferable that R A / R B It is more preferable that R ≧0.01. A / R B represents the rate of change in volume resistivity after storage, and R A / R B The larger and closer to 1.0, the smaller the change in volume resistance is and the better the heat resistance of the inductor element is.

[0037] In addition, the volume resistivity R before storage B is 1 x 10 12 It is preferable that the volume resistivity after storage is R A is 1 x 10 9The volume resistivity is preferably Ω·cm or more. The volume resistivity may be measured using a high resistance meter (for example, HP 4339B).

[0038] In the inductor element 100 of this embodiment, the above heat resistance can be achieved by including in the powder magnetic core an epoxy resin having two or more mesogen skeletons between the epoxy bonds. As a result, in the inductor element 100, energy loss can be reduced, and a smaller inductor and a larger current can be suitably achieved.

[0039] Next, an example of a method for manufacturing the inductor element 100 shown in FIG. 1 will be described.

[0040] First, a resin material, which is a raw material of the binder 2, and raw powder of the magnetic particles 4 are prepared. The raw powder of the magnetic particles 4 can be produced by a known powder production method. Examples of the powder production method include a gas atomization method, a water atomization method, a rotating disk method, and a carbonyl method. Alternatively, the raw powder may be produced by mechanically pulverizing a thin ribbon obtained by a single roll method. After obtaining the raw powder of the magnetic particles 4 by the above production method, the particle size of the magnetic particles 4 can be controlled by performing sieve classification or air flow classification. In addition, when forming an insulating coating on the surface of the magnetic particles 4, the raw powder obtained above may be subjected to a heat treatment or a surface treatment such as a phosphate treatment, a mechanical alloying treatment, a silane coupling treatment, or a hydrothermal synthesis.

[0041] An epoxy resin made of a prepolymer before curing is prepared as the resin raw material of the binder 2. This epoxy resin has at least two mesogen skeletons between two epoxy groups located at the ends of the prepolymer.

[0042] The epoxy resin and the curing agent are dissolved in a solvent to prepare a coating material. At this time, it is preferable to use a phenolic resin having a molecular weight of about 500 to 10,000, and it is preferable to use, for example, a biphenylaralkyl type curing agent or a p-xylylene type curing agent. The solvent is not particularly limited, and acetone, isopropyl alcohol (IPA), methyl ethyl ketone (MEK), butyl diglycol acetate (BCA), methanol, etc. can be used. Furthermore, a curing accelerator (curing catalyst), a lubricant, a flexibilizer, a plasticizer, a dispersant, a colorant, a sedimentation inhibitor, etc. may be appropriately added to the coating material. The amount of the curing agent to be added may be appropriately determined depending on the amount of the epoxy resin to be mixed.

[0043] Next, the raw powder of magnetic particles 4 and paint containing epoxy resin are put into various kneading machines such as a kneader or a twin-screw extruder and kneaded to produce a precursor for powder magnetic core. At this time, it is preferable to mix the raw powder and paint so that the binder 2 is 1 to 4 parts by mass per 100 parts by mass of magnetic particles. In addition, in this kneading process, non-magnetic ceramic particles and the like may be added as appropriate depending on the application of the inductor element.

[0044] Next, a powder magnetic core is manufactured using the precursor. In the case of the inductor element 100 shown in FIG. 1, the precursor is filled into a mold together with an air-core coil as an insert member, and compression molded. This results in a molded body having the shape of the powder magnetic core to be manufactured, and the epoxy resin in the molded body is cured by appropriately heat-treating the molded body. The heat treatment conditions at this time are not particularly limited, and may be conditions that sufficiently cure the epoxy resin. For example, the heat treatment temperature is 150°C to 200°C, and the treatment time is 1 hour to 5 hours. The atmosphere during the heat treatment is not particularly limited, and may be air.

[0045] Through the above steps, an inductor element 100 having a coil 120 embedded inside a powder magnetic core 110 is obtained.

[0046] (Summary of this embodiment) The powder magnetic core 110 of this embodiment has a binder 2 containing an epoxy resin and a phenol resin, and magnetic particles 4 dispersed in the binder 2. The epoxy resin contained in the binder 2 has at least two mesogen skeletons between two epoxy bonds that are adjacent along the molecular chain.

[0047] As a result of intensive research, the inventors of the present invention found that the number of mesogen skeletons present between epoxy bonds affects adhesion defects during warm molding. Specifically, according to experiments by the inventors of the present invention, when an epoxy resin having no mesogen skeleton or an epoxy resin having only one mesogen skeleton between epoxy bonds is used, the molded body is likely to stick to the mold during warm molding, and molding defects are likely to occur. Therefore, with these conventional epoxy resins, it was necessary to use a lubricant that could lead to a decrease in strength, or to manufacture the product by cold molding instead of warm molding. On the other hand, when an epoxy resin having at least two or more mesogen skeletons between epoxy bonds is used, adhesion defects during warm molding can be prevented. As a result, the dust core 110 according to this embodiment exhibits higher strength, relative permeability, and heat resistance than when a conventional epoxy resin is used.

[0048] The reason why the above effect is obtained is not entirely clear, but is thought to be related to steric hindrance due to multiple mesogenic skeletons.

[0049] In the inductor element 100 having the powder magnetic core 110, the volume resistance after storage at 175° C. for 100 hours is R A The volume resistance before storage is R B Then, R A / R B >0.001. As a result, in the inductor element 100 of this embodiment, energy loss can be reduced, and a smaller inductor and a larger current can be suitably achieved.

[0050] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made within the scope of the present invention.

[0051] For example, an electronic component such as an inductor element may be formed by combining a plurality of powder magnetic cores. The shape of the powder magnetic core is not particularly limited, and may be, for example, a toroidal type, an FT type, an ET type, an EI type, an UU type, an EE type, an EER type, an UI type, a drum type, a pot type, or a cup type. In the above embodiment, a coil is embedded in the powder magnetic core, but the arrangement of the coil is not limited to the configuration shown in FIG. 1, and the coil may be formed by winding a conductor around the outside of the powder magnetic core.

[0052] The method of manufacturing the powder magnetic core is not limited to the above-mentioned embodiment, and the powder magnetic core may be manufactured by a sheet method or injection molding, or may be manufactured by two-stage compression. In the manufacturing method using two-stage compression, for example, a precursor is temporarily compressed to produce a plurality of preforms, and then these preforms are combined with an air-core coil and finally compressed.

[0053] Furthermore, in the above embodiment, the inductor element 100 has been described, but the powder magnetic core of the present invention can also be applied to electronic components such as reactors, transformers, contactless power transfer devices, and magnetic shielding components. EXAMPLES

[0054] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the following examples.

[0055] Examples 1 to 16 In this example, inductor samples according to Examples 1 to 16 were manufactured in the following procedure.

[0056] First, Fe-4.5Si alloy powder was prepared by gas atomization as the raw material powder of the magnetic particles 4. A SiO2 film having an average thickness of about 100 nm was formed on the surface of this raw material powder by heat treatment.

[0057] Next, a biphenyl-type epoxy resin made of a prepolymer was prepared. The epoxy resin had multiple mesogenic skeletons represented by formula (I) between the epoxy groups located at the ends of the prepolymer. Specifically, the number of mesogenic skeletons between the epoxy groups was 2 in Examples 1 to 3, 3 in Examples 4 to 7 and 14, 10 in Examples 8 to 10 and 15, and 20 in Examples 11 to 13 and 16.

[0058] The epoxy resin and the curing agent were dissolved in an acetone solvent to obtain a coating material. In this case, a biphenylaralkyl type curing agent A was used in Examples 1 to 13, and a p-xylylene type curing agent B was used in Examples 14 to 16. In addition, the amount of the curing agent added was 50 parts by mass per 100 parts by mass of the epoxy resin in each Example, and 1 part by mass of a curing accelerator was added per 100 parts by mass of the epoxy resin.

[0059] Next, the above-mentioned paint and Fe-4.5Si alloy powder were kneaded in a kneader to obtain the precursors for powder magnetic cores according to Examples 1 to 16. At this time, the compounding ratio of the paint to the alloy powder was adjusted so that the content of the binder 2 per 100 parts by mass of the magnetic particles was within the range of 1 to 5 parts by mass.

[0060] Next, the precursor was put into a mold and compression molded to obtain a toroidal-shaped molded body. Compression molding was performed by both cold molding and warm molding, and samples manufactured by cold molding and warm molding were obtained for each Example. Cold molding was performed at a molding pressure of 8.0 MPa, and warm molding was performed under conditions of a molding pressure of 4.0 MPa and a mold temperature of 110°C. After compression molding, the molded body was heated at 180°C for 3 hours to harden the epoxy resin in the molded body, thereby obtaining powder core samples according to Examples 1 to 16. The manufactured toroidal mold had an outer diameter of 17.5 mm and an inner diameter of 10.0 mm, and the powder core sample was manufactured by weighing out a weight of 5.0 g. The manufactured powder core sample had a thickness (height) of about 5 mm.

[0061] The dust core samples of the respective examples were subjected to the following evaluations.

[0062] (Measurement of the number of mesogenic skeletons) An analytical sample for molecular structure analysis was taken from the prepared powder core sample. Then, NMR, FT-IR, GC / MS, and LC / MS were performed to analyze the molecular structure of Binder 2 and to identify the number of mesogen skeletons present between two adjacent epoxy bonds.

[0063] (Analysis of powder cores) In addition, the powder core samples were analyzed by ICP-AES to measure the amount of binder contained in the powder core. The content of binder 2 per 100 parts by mass of magnetic particles was calculated from the intensity of the measured elements. As a result, it was confirmed that the content of binder 2 in each example was as targeted at the time of manufacture and was approximately the same as the compounding ratio of the epoxy resin in the precursor.

[0064] During cross-sectional observation by SEM, the average particle size (D50) and average circularity of the magnetic particles 4 were measured. As a result, in all of the Examples, the average particle size was in the range of 20 to 40 μm, and the average circularity was 0.95 or more.

[0065] (Ring crushing strength test) The strength of the powder magnetic core was evaluated by performing a radial crushing strength test based on JIS Z 2507 and calculating the radial crushing strength. When the radial crushing strength was 120 MPa or more, the strength characteristics of the sample was determined to be good.

[0066] (Measurement of relative permeability) In addition, a conducting wire was wound 30 turns around the manufactured toroidal dust core sample to produce an inductor element, and its relative permeability was measured. The relative permeability was measured as shown below. Using an LCR meter and a DC bias power supply, the inductance was measured at a frequency of 100 kHz and a DC superimposed magnetic field of 50 mT, and the relative permeability at room temperature was calculated from the inductance. A relative permeability of 25 or more was considered to be acceptable, 26 or more was considered to be good, and 28 or more was considered to be particularly good.

[0067] (Heat resistance evaluation) In the heat resistance test, the inductor element was kept at 175°C for 100 hours, and the rate of change in volume resistance before and after the test was measured. A The volume resistance before storage is R B As R in each example A / R B was calculated. R A / R B The higher the R, the better the heat resistance. A / R B >0.001 is acceptable, R A / R B A value of 0.01 or more was judged to be particularly good. The volume resistivity was measured using a high resistance meter (HP 4339B) by applying a probe of Φ1.0 mm parallel to the thickness direction.

[0068] Comparative Examples 1 to 3 In Comparative Example 1, a dust core sample was produced using an o-cresol novolac type epoxy resin that does not have a mesogenic skeleton. In Comparative Example 2 and Comparative Example 3, a dust core sample was produced using a biphenyl type epoxy resin in which the number of mesogenic skeletons present between adjacent epoxy bonds is only one. In Comparative Example 2, a biphenyl aralkyl type curing agent A was used, and in Comparative Example 3, a p-xylylene type curing agent B was used. Thus, in Comparative Examples 1 to 3, the type of epoxy resin used was changed, but the experimental conditions other than the type of epoxy resin were the same as in the above examples, and the same evaluations were performed as in each example.

[0069] The evaluation results of each of the examples and comparative examples are shown in Table 1. [Table 1]

[0070] As shown in Table 1, in Comparative Example 1, which has no mesogenic skeleton, and Comparative Examples 2 and 3, which have only one mesogenic skeleton, the radial crushing strength was less than 120 MPa, and did not satisfy the pass / fail criteria for strength. A / RB was 0.001 or less, and the heat resistance pass / fail criteria were not satisfied. Furthermore, in Comparative Examples 1 to 3, poor adhesion to the die occurred during warm forming, making it difficult to obtain non-defective products. That is, in Comparative Examples 1 to 3, it was not possible to evaluate the properties of the warm-formed samples, and only a manufacturing method using cold forming could be applied.

[0071] On the other hand, in Examples 1 to 16 in which the number of mesogenic skeletons present between epoxy bonds is two or more, when produced by cold molding, higher strength was obtained than in Comparative Examples 1 to 3, and the heat resistance pass / fail criteria were satisfied. From this result, it was found that by making the number of mesogenic skeletons present between epoxy bonds multiple, rather than single, it is possible to simultaneously achieve high strength, high relative magnetic permeability, and high heat resistance.

[0072] Furthermore, in Examples 1 to 16, adhesion defects during warm compaction could be suppressed, and warm compaction yielded dust cores with higher strength and relative permeability than cold compaction. From these results, it was found that by making the number of mesogen skeletons present between epoxy bonds multiple, rather than single, molding defects can be dramatically suppressed, and each characteristic (strength, relative permeability, heat resistance) can be improved more efficiently.

[0073] Moreover, by comparing the evaluation results of each Example, it was confirmed that the smaller the binder content in the powder magnetic core, the higher the relative magnetic permeability tends to be, and the higher the binder content, the higher the strength tends to be. It was also found that when the binder content is 1 to 4 parts by mass, it is possible to improve the strength and magnetic properties in a well-balanced manner. Furthermore, from the results of Example 7, it was confirmed that when the binder content is more than 4 parts by mass, the magnetic permeability tends to decrease. From the above results, it was found that the binder content per 100 parts by mass of metal magnetic particles is preferably within the range of 1 to 4 parts by mass. [Explanation of symbols]

[0074] 100 … Inductor element 110 … powder magnetic core 2 … Binder 4 … Magnetic particles 4a … large particles 4b … Small particles 120 ... Coil

Claims

1. A binder including an epoxy resin and magnetic particles dispersed in the binder, The epoxy resin has 3 to 100 mesogen skeletons between two epoxy bonds that are adjacent along a molecular chain.

2. the magnetic particles are metal magnetic particles, 2. The dust core according to claim 1, wherein a content of the binder relative to 100 parts by mass of the metal magnetic particles is 1.0 part by mass or more and 4.0 parts by mass or less.

3. The powder magnetic core according to claim 1 or 2, wherein the mesogenic skeleton has a structure represented by the following formula (I): 【Chemistry 1】 (In formula (I), Y is selected from -H, an alkyl group (an aliphatic hydrocarbon having 4 or less carbon atoms), an acetyl group, and a halogen, and all Y in the mesogenic skeleton may be the same or different. * indicates a bonding site with an adjacent atom.)

4. An inductor comprising the powder magnetic core according to any one of claims 1 to 3.

5. The volume resistance of the inductor after storing it at 175° C. for 100 hours is R A and the volume resistance before storage is R B As, R A / R B The inductor according to claim 4 , which satisfies >0.001.

Citation Information

Patent Citations

  • Reactive curing-type resin and composition thereof

    JP2007051221A

  • Precursor for powder magnetic core, powder magnetic core, and electronic component

    JP2016012671A

  • Curable resin composition and cured product of the same

    JP2021031523A

  • Resin powder, sealing material, electronic component, and resin powder manufacturing method

    WO2019193959A1